Antibakteri Sari Pati Tumbuhan Kelor (Moringa oleifera) terhadap Zona Hambat Bakteri Salmonella typhi - Nindia Saputri; Fitria Lestari; Ria Dwi Jayati (Universitas PGRI Silampari, 2025)
This study aims to determine the antibacterial results of Moringa plant extract (Moringa oleifera) against the inhibition zone of Salmonella typhi bacteria. The research method used is the treatment applied consisted of an extract Data collection techniques by measuring the inhibition zone formed with a caliper. Data analysis techniques use quantitative statistics from the results of the inhibition zone measurements. The results of the study showed that there was antibacterial activity of Moringa plant extract (Moringa oleifera) against the inhibition zone of Salmonella typhi bacteria. Based on the results of the Kruskal Wallis test, the results showed that Sig <α, 0.00 <0.05, which means that it shows significant results, indicating that the administration of Moringa plant extract (Moringa oleifera) has an effect on the inhibition zone of Salmonella typhi bacteria. so it is concluded that administration of Moringa oleifera leaf extract has an effect on the inhibition zone of Salmonella typhi bacteria.